Main Directions of Higher Education Regionalization Process as an Integral Part of Social Partnership in Society (the Problems of Inclusive Education) - A. Nazarenko, M.; V. Kurenkov, V.; V. Muravev, V.; S. Novikov, A.; A. Baranova, I. (International Journal of Engineering and Technology, 2018)
The key problem of current Russian regional economics is a shortage of professionals.  The aim of Higher Education Institution of Inclusive Education is to build such a system of social partnership, which would include all structures fascinated in qualified professionals. Education regionalization processes need to be spread to all structures that make up the system of social partnership, so that regional universities’ graduates would strive to work in their home region and in order for them to be able to meet professional standards. Authors concluded that standardization would provide an ability to create comprehensive student assessment that will allow businesses to recruit employees that match their requirements better.